2002
DOI: 10.1161/hc0402.102929
|View full text |Cite
|
Sign up to set email alerts
|

Fosinopril Versus Amlodipine Comparative Treatments Study

Abstract: Background-ACE inhibitors and calcium antagonists may modulate fibrinolysis. We conducted a randomized controlled trial to assess the effects of these drugs on plasminogen activator inhibitor-1 (PAI-1) antigen, an inhibitor of fibrinolysis. Methods and Results-Participants with hypertension and type 2 diabetes mellitus (nϭ96, 51% black) were randomized after an initial 4 weeks of placebo to double-blind 20 or 40 mg fosinopril or 5 or 10 mg amlodipine daily for 4 weeks in a fixed-dose regimen. After 4 weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 25 publications
3
26
3
Order By: Relevance
“…When patients who received lisinopril were analyzed by dose level, postoperative PAI-1 antigen concentrations were suppressed in patients taking 20 to 40 mg/d lisinopril but not in patients taking Յ10 mg/d. This finding is in agreement with the findings of Pahor et al, 13 who demonstrated that fosinopril reduces PAI-1 in a dose-dependent fashion.…”
Section: Study Limitationssupporting
confidence: 93%
See 2 more Smart Citations
“…When patients who received lisinopril were analyzed by dose level, postoperative PAI-1 antigen concentrations were suppressed in patients taking 20 to 40 mg/d lisinopril but not in patients taking Յ10 mg/d. This finding is in agreement with the findings of Pahor et al, 13 who demonstrated that fosinopril reduces PAI-1 in a dose-dependent fashion.…”
Section: Study Limitationssupporting
confidence: 93%
“…Nevertheless, all but 3 patients were taking lisinopril. Moreover, previously published reports that enalapril, 33 quinapril, 8 and ramipril 9 (carboxyl-containing ACEIs like lisinopril), fosinopril 13 (a phosphinyl-containing ACEI), and captopril 34 (a sulfhydryl-containing ACEI) all decrease PAI-1 concentrations suggest that the effect of ACE inhibition on PAI-1 is a class effect. The finding that lisinopril decreased postoperative PAI-1 in the present study confirms a study by Shinosaki et al, 35 who reported that lisinopril suppressed PAI-1 expression in an animal model of mesangioproliferative nephritis but conflicts with a study by Zehetgruber et al, 36 who reported no effect of lisinopril on fibrinolysis.…”
Section: Study Limitationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Falls in SBP (-6.02 mmHg, 4.19 % at 12 weeks) is less while falls in DBP (-8.07 mmHg, 9.05 %) is more as reported by Pahor M, et al (10 mmHg and 5 mm of Hg respectively, at 8 weeks in patients of T2DM with hypertension). 12 While, at 24 weeks both SBP and DBP fall is more in this study as compared to Zaman ZA, et al (14 mm Hg (8.43%) and 8 mm Hg (8.16%) in patients of hypertension with or without T2DM at 24 weeks). 13 In comparison to Agodoa LY, et al both SBP and DBP fall is less at 12 weeks (6.02 mmHg and 8.07 mmHg) while more fall is seen in both these BP at 24 weeks (20.76 mmHg and 10 mmHg respectively at 12 and 24 weeks) in this study.…”
Section: Group Acontrasting
confidence: 56%
“…23 The effects of calcium antagonists on fibrinolysis have been poorly studied and conflicting data have been reported with some studies demonstrating that calcium antagonists improve 24 and others showing impairment of fibrinolytic function. 25,26 Finally, the unfavourable effect of hydrochlorothiazide on fibrinolysis has previously been observed. 23 In the study by Mugellini et al, 18 it is of note that there were no statistical differences in blood pressure-lowering efficacy between both combinations of antihypertensive drugs with no changes in the whole study period.…”
mentioning
confidence: 91%